(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Public-private partnership (from now on – PPP) in the field of healthcare is quite well-known in the Western world (Great Britain, Germany, USA, etc.) interaction and is relatively “young” for Russia. But despite this, the PPP sphere is widely discussed in the public field of the Russian political establishment, and the need to use PPP tools in the implementation of investment projects is reflected in government programs and development strategies. It suggests that the development of PPP is supported at the country’s political leadership level.